Knowledge Translation of the Gross Motor Function Classification System Among Pediatric Physical Therapists. Issue 4 (2015) - Deville, Caitlin; McEwen, Irene; Arnold, Sandra H.; Jones, Maria; Zhao, Yan D.
Abstract : Purpose: To learn where pediatric physical therapists in the United States are in the process of knowledge translation of the Gross Motor Function Classification System (GMFCS). Methods: Links to an online survey were distributed electronically. Results: All 283 respondents reported hearing about the GMFCS, 95% agreed it was useful, 81% reported they were confident in their ability to use it, 77% reported they use it, and 42% reported they use it consistently. Therapists primarily used the GMFCS to predict gross motor function, set realistic goals, and anticipate need for assistive technology. The American Physical Therapy Association Section on Pediatrics members were more likely than nonmembers to agree the GMFCS is useful, they are able to use it, that they use it, and that they use it consistently. Conclusions: The majority of therapists responding use the GMFCS, but not consistently. Video Abstract: For more insights from the authors, see Supplemental Digital Content 1, available athttp://links.lww.com/PPT/A91 . Abstract : Supplemental Digital Content is Available in the Text.Therapists primarily use the GMFCS to predict gross motor function, set realistic goals, and anticipate need for assistive technology. The majority of therapists use the GMFCS, but not consistently.